2007
DOI: 10.1016/j.febslet.2007.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosative stress in plants

Abstract: Nitrosative stress has become a usual term in the physiology of nitric oxide in mammalian systems. However, in plants there is much less information on this type of stress. Using olive leaves as experimental model, the effect of salinity on the potential induction of nitrosative stress was studied. The enzymatic L L-arginine-dependent production of nitric oxide (NOS activity) was measured by ozone chemiluminiscence. The specific activity of NOS in olive leaves was 0.280 nmol NO mg À1 protein min À1 , and was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
229
0
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 319 publications
(250 citation statements)
references
References 48 publications
13
229
0
8
Order By: Relevance
“…Additionally, it was demonstrated that peroxisomal NO generation was sensitive to animal NOS inhibitors and was calcium dependent. This data is in line with the biochemical evidence on the presence of NOS activity reported in pea leaf peroxisomes Corpas et al, 2004), olive (Olea europaea) leaf (Valderrama et al, 2007), and sunflower (Helianthus annuus) hypocotyls (Chaki et al, 2009a). It is worth noting that some of the cofactors involved in the L-Arg-dependent NOS activity in plant peroxisomes have been described in previous studies (Corpas et al, 2009b).…”
Section: Pex12 and Pex13 Appear To Be Involved In The Peroxisomal Impsupporting
confidence: 79%
See 2 more Smart Citations
“…Additionally, it was demonstrated that peroxisomal NO generation was sensitive to animal NOS inhibitors and was calcium dependent. This data is in line with the biochemical evidence on the presence of NOS activity reported in pea leaf peroxisomes Corpas et al, 2004), olive (Olea europaea) leaf (Valderrama et al, 2007), and sunflower (Helianthus annuus) hypocotyls (Chaki et al, 2009a). It is worth noting that some of the cofactors involved in the L-Arg-dependent NOS activity in plant peroxisomes have been described in previous studies (Corpas et al, 2009b).…”
Section: Pex12 and Pex13 Appear To Be Involved In The Peroxisomal Impsupporting
confidence: 79%
“…10D). In a previous work involving olive plant growth under salinity (200 mM NaCl) stress conditions, similar behavior was observed, with an increase in the number and intensity of leaf proteins undergoing Tyr nitration (Valderrama et al, 2007). In this context, it must be mentioned that a rise in protein Tyr nitration is considered an indicator of ONOO 2 activity and a marker of pathological diseases and oxidative stress in animals (Ischiropoulos, 1998; Radi 2004;Szabó et al, 2007) and plants (Corpas et al, 2007b(Corpas et al, , 2008(Corpas et al, , 2009cChaki et al, 2009a).…”
Section: Peroxisomes Release No Under Salinity Stress That Is Involvementioning
confidence: 57%
See 1 more Smart Citation
“…However, when plants are exposed to different types of stress, the production of ROS and RNS can overwhelm the scavenging capacity of the cell, thereby leading to accumulation of these reactive molecules with the establishment of oxidative stress conditions (Apel and Hirt, 2004;Møller et al, 2007;Valderrama et al, 2007;Corpas et al, 2008). Interestingly, multiple MAPK modules that mediate oxidative stress responses are not only induced by ROS, but can also regulate ROS levels by stimulating catalase activities (Rodriguez et al, 2010).…”
mentioning
confidence: 99%
“…66,67 Salinity-induced nitrosative stress in olive leaves revealed an increment in Nitric Oxide Synthase (NOS)-dependent NO liberation followed by accumulation of RNS in vascular bundles. 68 Based on investigations in animal systems, it is evident that melatonin acts as a mediator of ROS and RNS crosstalk under nitrosative stress. Melatonin reacts with nitrogen centered radicals to produce nitrosated products such as N-nitrosomelatonin, which is formed due to reaction of NO with melatonin.…”
Section: Mechanism Of Quenching Of Ros By Melatoninmentioning
confidence: 99%